LOST IN TRANSLATION AND THE CRUCIAL PROCESS OF CONVENTION - W Witriani; Ulyati Retno Sari; Fuad Arif Fudiyartanto (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT Certificates, academic transcripts, and name of institutions are such very important academic documents for any institutions, including educational institutions, which translation into foreign languages (for example into English) should be done carefully, thoroughly, and precisely. This research on the translation of such academic documents in UIN Sunan Kalijaga Yogyakarta found that, although in general the translations are correct, there are many parts of the documents that have not been properly translated. Inaccuracies occurs due to frequent inconsistencies in choosing the diction (or vocabulary), phrase structures, and inappropriate choices of the translation procedures. Therefore, the alignment, uniformity, and convention of the translations are necessary to maintain the quality of the results. ABSTRAK Sertifikat, transkrip akademik, dan nama institusi adalah dokumen akademis yang sangat penting bagi institusi manapun, termasuk institusi pendidikan, yang ketika diterjemahkan ke bahasa asing (misalnya bahasa Inggris) harus dilakukan dengan hati-hati, teliti, dan tepat. Penelitian ini tentang penerjemahan dokumen akademis tersebut di UIN Sunan Kalijaga Yogyakarta menemukan bahwa, walaupun secara umum terjemahannya benar, ada banyak bagian dokumen yang belum diterjemahkan secara takurat. Ketidakakuratan tersebut terjadi karena sering terjadi ketidakkonsistenan dalam memilih diksi (atau kosa kata), struktur frase, dan pilihan prosedur terjemahan yang tidak sesuai. Oleh karena itu, keselarasan, keseragaman, dan konvensi terjemahan diperlukan untuk menjaga kualitas hasil. How to Cite: Witriani. Sari, U. R. Fudiyartanto, F. A. (2017). Lost In Translation and the Crucial Process of Convention. IJEE (Indonesian Journal of English Education), 4(1), 93-110 doi:10.15408/ijee.v4i1.6598.DOI: http://dx.doi.org/10.15408/ijee.v4i1.6598